PSYCHOLOGICAL FEATURES OF FORMATION OF LOCUS OF CONTROL IN ADOLESCENTS (TAMADDUN NURI JURNALI, 2024)
This article reveals the concept of subjective control, i.e. locus control, its incomparable place in a person’s life, as well as a method aimed at determining the level of locus control, and the subjective control of high school students is studied, the results are described and analyzed. The level of subjective control is one of the most important characteristics of self-awareness; it determines the characteristics of behavioral reactions in a wide range of social interaction and manifests itself in a sense of responsibility, level of activity and influence on living conditions.